Evidence of Late Ediacaran Hyperextension of the Laurentian Iapetan Margin in the Birchy Complex, Baie Verte Peninsula, Northwest Newfoundland:: Implications for the Opening of Iapetus, Formation of Peri-Laurentian Microcontinents and Taconic – Grampian Orogenesis - van Staal, Cees; Chew, Dave; Zagorevski, Alexandre; McNicoll, Vicki; Hibbard, James; Skulski, Tom; Castonguay, Sébastien; Escayola, Monica; Sylvester, Paul (Geoscience Canada, 2013)
SUMMARY The Birchy Complex of the Baie Verte Peninsula, northwestern Newfoundland, comprises an assemblage of mafic schist, ultramafic rocks, and metasedimentary rocks that are structurally sandwiched between overlying ca. 490 Ma ophiolite massifs of the Baie Verte oceanic tract and underlying metasedimentary rocks of the Fleur de Lys Supergroup of the Appalachian Humber margin. Birchy Complex gabbro yielded a Late Ediacaran U–Pb zircon ID–TIMS age of 558.3 ± 0.7 Ma, whereas gabbro and an intermediate tuffaceous schist yielded LA–ICPMS concordia zircon ages of 564 ± 7.5 Ma and 556 ± 4 Ma, respectively. These ages overlap the last phase of rift-related magmatism observed along the Humber margin of the northern Appalachians (565–550 Ma). The associated ultramafic rocks were exhumed by the Late Ediacaran and shed detritus into the interleaved sedimentary rocks. Psammite in the overlying Flat Point Formation yielded a detrital zircon population typical of the Laurentian Humber margin in the northern Appalachians. Age relationships and characteristics of the Birchy Complex and adjacent Rattling Brook Group suggest that the ultramafic rocks represent slices of continental lithospheric mantle exhumed onto the seafloor shortly before or coeval with magmatic accretion of mid-ocean ridge basalt-like mafic rocks. Hence, they represent the remnants of an ocean – continent transition zone formed during hyperex-tension of the Humber margin prior to establishment of a mid-ocean ridge farther outboard in the Iapetus Ocean. We propose that microcontinents such as Dashwoods and the Rattling Brook Group formed as a hanging wall block and an extensional crustal allochthon, respectively, analogous to the isolation of the Briançonnais block during the opening of the Alpine Ligurian–Piemonte and Valais oceanic seaways.